2009
DOI: 10.1002/ange.200903969
|View full text |Cite
|
Sign up to set email alerts
|

A Formal Carbon–Sulfur Triple Bond: HCSOH

Abstract: Äußerst selten: Eine CS‐Dreifachbindung kann für HCSOH angenommmen werden, das aus H2CSO durch eine photochemische [1,3]H‐Verschiebung zugänglich wurde. Aber ist diese formale Beschreibung in Einklang mit dem, was aus IR‐Schwingungen, Bindungslängen, Bindungsordnungen, Molekülorbitalen und Komplianzkonstanten folgt? Solche Moleküle sind eine Herausforderung für unser derzeitiges Verständnis der chemischen Bindung und verfeinern es.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…The desired output of the device is mathematically shown to be temperature independent. However, the presented device uses an IL that has reported high temperature/viscosity relation 30,32 and thus a high Temperature Coefficient of Impedance (TCZ). 33 In our previous work we have shown that [BMIM] + [BF 4 ] À IL is capable of a very high TCZ of up to À17 300 ppm K À1 .…”
Section: Resultsmentioning
confidence: 99%
“…The desired output of the device is mathematically shown to be temperature independent. However, the presented device uses an IL that has reported high temperature/viscosity relation 30,32 and thus a high Temperature Coefficient of Impedance (TCZ). 33 In our previous work we have shown that [BMIM] + [BF 4 ] À IL is capable of a very high TCZ of up to À17 300 ppm K À1 .…”
Section: Resultsmentioning
confidence: 99%
“…Mloston’s research interests are in heterocyclic systems, sulfur compounds, fluorine‐containing organic compounds, reactive intermediates, and asymmetric catalysis. He has reported in Angewandte Chemie on a carbon–sulfur triple bond,3a and in the European Journal of Organic Chemistry on 1,2,4‐trithiolane‐ S ‐oxides 3b…”
Section: Awarded …︁mentioning
confidence: 99%
“…Mlostons Interesse gilt heterocyclischen Systemen, Schwefelverbindungen, fluorhaltigen organischen Verbindungen, reaktiven Zwischenstufen und der asymmetrischen Katalyse. In der Angewandten Chemie berichtete er über eine Kohlenstoff‐Schwefel‐Dreifachbindung3a und im European Journal of Organic Chemistry über 1,2,4‐Trithiolan‐ S ‐oxide 3b…”
Section: Ausgezeichnet …︁unclassified